Fresno County Young Lawyers Association 8th Annual Channel 18 Law Quiz Program - Watkins, Howard::::::::: (1988)
Fresno County Bar Association President Herbert Levy overlooking volunteer attorneys taking call-in questions; Front: Tracie Dudley, Fresno County Young Lawyers Association President Brad Hill, Jack Hames, and Joanne Sanoian; Back Row: Rene Lastreto II, Sandra Snyder, Kent Klassen, William J. Smith, and Howard Zidenberg